Can a rapid mobility transition appear both desirable and achievable? Reflections on the role of competing narratives for socio-technical change and suggestions for a research agenda - Lisa Ruhrort (Innovation: The European Journal of Social Science Research, 2022)
As research on socio-technical transitions has repeatedly shown, positive or negative narratives can play a key role in galvanizing public support for or resistance against socio-technical transitions. In the mobility sector, many countries have recently seen some indications of beginning socio-technical change dynamics. In the case of Germany, key practices of a low-carbon transport system – such as cycling, substitution of travel through home office or 'shared mobility services' – are moving from niches to mainstream, while grassroots initiatives are successfully demanding improvements for cycling and walking. In this dynamic situation competing narratives of change begin to emerge, which claim to define what a transition towards 'sustainable' mobility should look like and how it could be accomplished. Against the backdrop of these recent discursive shifts the article highlights three key conflictual dimensions, along which competing narratives of a mobility transition in Germany, but also in other European countries, are likely going to diverge. The article suggests that research into mobility transitions should focus on the intensifying discursive struggles, in which different social groups with highly differing power will attempt to shape the broader socio-technical vision of a 'sustainable' mobility future.
Keywords: 300; mobility; transport; sustainability transition; narratives; socio-technical transition